Characteristics and Mechanisms of Long-lived Concentric Eyewalls in Typhoon Lekima in 2019 - Liu Tao; Duan Yihong; Feng Jianing; Wang Hui (应用气象学报)
The structure change of typhoon eyewall has important influences on tropical cyclone (TC) intensity, and it brings great difficulties to TC intensity forecast. Compared to the TC with only one eyewall, the dynamic and physical processes controlling the intensity change of concentric eyewalls are much more complex. Strengthening the research on this type of typhoons is conducive to improve the understanding of the structure and intensity change of TC. Recently, the process of eyewall replacement cycle (ERC) is well understood, but the mechanism of concentric eyewalls maintenance (CEM) remains unclear. Therefore, it is necessary to use a variety of observation data, numerical model, and data assimilation methods to analyze real typhoons to further explore the mechanism of CEM.The evolution of concentric eyewalls in Typhoon Lekima in 2019 is analyzed with CIMSS microwave satellite images, Wenzhou Doppler radar in China and Ishigaki radar in Japan. Observational analysis indicates that secondary eyewall formation (SEF) happens at about 0600 UTC 8 August 2019. Unlike most concentric-eyewall typhoons, Typhoon Lekima has not undergone ERC, and the concentric eyewalls in Typhoon Lekima maintains for 35 hours.Meanwhile, a numerical experiment of Typhoon Lekima is performed using a WRF-based ensemble Kalman filtering (EnKF) data assimilation system. The evolution process of Typhoon Lekima is reproduced by the results of the analysis after assimilating the Ishigaki radar radial wind, and the simulated track, intensity, and structure are basically consistent with observational analysis. Therefore, based on the EnKF analysis fields, evolution characteristics of three-dimensional eyewalls structure in Typhoon Lekima are further analyzed. The results show that, in the initial stage of SEF, the inertial stability of the middle and lower layers of typhoon is high, and the thermal conditions of the environmental are conducive to the development of Typhoon Lekima. However, due to the strong vertical wind shear (VWS) and dry air intrusion in the mid-upper level, the outer eyewall has a weakening and asymmetric process. In addition, the maintenance mechanism of persistent concentric eyewalls is studied from the perspective of transverse circulation. The Sawyer-Eliassen diagnose is performed to investigate the transverse circulation and to reveal that the interference between the convection/subsidence couplet of the inner and outer eyewalls transverse circulation is not obvious so that the convection of the inner eyewall is not inhibited by the outer eyewall, and the inner eyewall maintains. Under the condition of strong VWS, the asymmetric outer eyewall cannot continuously enhance or contract and replace the inner eyewall, the structure of concentric eyewalls can be maintained for a long time. The structure of the outer eyewall and the distribution of transverse circulation in Typhoon Lekima play an important role in the maintenance of concentric eyewalls.